If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3(4x + -14) = 112 Reorder the terms: 2x + 3(-14 + 4x) = 112 2x + (-14 * 3 + 4x * 3) = 112 2x + (-42 + 12x) = 112 Reorder the terms: -42 + 2x + 12x = 112 Combine like terms: 2x + 12x = 14x -42 + 14x = 112 Solving -42 + 14x = 112 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '42' to each side of the equation. -42 + 42 + 14x = 112 + 42 Combine like terms: -42 + 42 = 0 0 + 14x = 112 + 42 14x = 112 + 42 Combine like terms: 112 + 42 = 154 14x = 154 Divide each side by '14'. x = 11 Simplifying x = 11
| 6x+3x+7.3=5+35.2 | | 4y+x=5(2x-y) | | 6x+4(-4x-14)=-176 | | 5m^2-50m=0 | | 4x+3(-3x+13)=89 | | 7+(-5)=12 | | 0=0.3*4180*(t-20)+0.1*385*(t-400) | | x-3x+5=3x-0.5 | | 2x+3*2=5x+4 | | x-3x+5=3x-1 | | 5m(2m^2-n^3)= | | (5n-18)+(2n+12)=180 | | 3+5x=x+15 | | (4x-1)(x-9)=0 | | -3(m+4)=4 | | y=(7x+9)(x-1) | | 105=-3x+5(-3x+3) | | 7m-3m+4=16 | | 5lnx=30 | | 18y=12-12x | | =2500-2x | | 7x-6=3(x^6) | | (12x+10)-(-4x-6x+10)= | | 6[-6x+6+4x(x+1)]=6x+2 | | 0.5x+0.25=x | | 3x+3(5x-10)=138 | | (2mn+8m^2n-5n+6m)= | | 0=(t-20)+(t-400) | | 8.57x+17.14=34.28 | | t-20=t-400 | | (2mn+8m^2n-5n+6m)(10mn^2)= | | 3cos(x)=8-4sec(x) |